Comparing Ethnicity-Specific Reference Intervals for Clinical Laboratory Tests from EHR Data. (23rd October 2019) - Rappoport, Nadav; Paik, Hyojung; Oskotsky, Boris; Tor, Ruth; Ziv, Elad; Zaitlen, Noah; Butte, Atul J
Abstract: Background: The results of clinical laboratory tests are an essential component of medical decision-making. To guide interpretation, test results are returned with reference intervals defined by the range in which the central 95% of values occur in healthy individuals. Clinical laboratories often set their own reference intervals to accommodate variation in local population and instrumentation. For some tests, reference intervals change as a function of sex, age, and self-identified race and ethnicity. Methods: In this work, we develop a novel approach, which leverages electronic health record data, to identify healthy individuals and tests for differences in laboratory test values between populations. Results: We found that the distributions of >50% of laboratory tests with currently fixed reference intervals differ among self-identified racial and ethnic groups (SIREs) in healthy individuals. Conclusions: Our results confirm the known SIRE-specific differences in creatinine and suggest that more research needs to be done to determine the clinical implications of using one-size-fits-all reference intervals for other tests with SIRE-specific distributions.